2017
DOI: 10.1177/1010428317713674
|View full text |Cite
|
Sign up to set email alerts
|

The role of Capon in multiple myeloma

Abstract: Capon is a ligand protein of nitric oxide synthase 1. Recently, studies have shown that Capon is involved in the development of tumors. It is independent of the regulation of nitric oxide synthase 1 in this process. At the same time, studies have found that nitric oxide synthase 1 is expressed in multiple myeloma, but its role in the development and progression of myeloma remains unclear. In this study, we found that there was a different expression of Capon between the normal multiple myeloma cells and the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Other TAU interacting proteins with strong relevance for cancer are the carboxyl-terminal PDZ ligand of neuronal nitric oxide synthase protein CAPON [225], the probable ATP-dependent DEAD-Box RNA helicase DDX6 [226], the proto-oncogene tyrosine-protein kinase SRC [227], the tyrosine-protein kinase ABL1 [228], the dual specificity tyrosine-phosphorylation-regulated kinase 1A DYRK1A [229], the EWS RNA-binding protein 1 (EWSR1) [230] and the sirtuin family [231].…”
Section: Protein-protein Interactions Linking Tau To Cancermentioning
confidence: 99%
“…Other TAU interacting proteins with strong relevance for cancer are the carboxyl-terminal PDZ ligand of neuronal nitric oxide synthase protein CAPON [225], the probable ATP-dependent DEAD-Box RNA helicase DDX6 [226], the proto-oncogene tyrosine-protein kinase SRC [227], the tyrosine-protein kinase ABL1 [228], the dual specificity tyrosine-phosphorylation-regulated kinase 1A DYRK1A [229], the EWS RNA-binding protein 1 (EWSR1) [230] and the sirtuin family [231].…”
Section: Protein-protein Interactions Linking Tau To Cancermentioning
confidence: 99%
“…Silencing CAPON enhanced anchorage- independent growth in breast cancer cells 18. In addition, interference with CAPON expression promoted the proliferation of multiple myeloma cells 19. We previously reported that overexpression of CAPON-S inhibited cell proliferation and decreased the activity of AKT signaling in U87 cells 20.…”
Section: Introductionmentioning
confidence: 93%
“…However, this effect is not present in U87 cells, while overexpression of CAPON-S inhibits Akt signaling in U87 cells [112]. Shen et al found that CAPON overexpression was associated with myeloma cell adhesion, cell growth, and cell-adhesion-mediated drug resistance [113]. A decrease in CAPON expression level not only induces the expression of Akt and p-Akt, but also increases cell adhesion and shortens the cellular G1 cycle.…”
Section: Capon Affects Tumor Growthmentioning
confidence: 99%
“…Acute brain injury [27,97,98] Acute spinal cord injury [99] Neurodegenerative diseases Alzheimer's disease [25,57] Huntington's disease [117,118] Parkinson's disease [100] Amyotrophic lateral sclerosis [101] Major depressive disorder [102,107] Bipolar disorder [102] Anxiety disorders [33,103,107] Post-traumatic stress disorder [104,105] Schizophrenia Schizophrenia [40,110,111] Cerebrovascular disease Ischemic stroke [27,99] Skeletal muscle disease Duchenne muscular dystrophy [36,116] Cancer Glioma [67,112] Myeloma [112,113] Breast cancer [67,114]…”
Section: Dendritic Development Of Neurons In the Brainmentioning
confidence: 99%